Aspen wood sawdust and its biocomposites applications - Anthonette, James; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Jamal, Uddin; Kuok, Kuok King; Mohammed Muzibur, Rahman; Muhammad Khusairy, Bakri (Elsevier Ltd., 2024)
Aspen trees or quaking aspen trees are medium sized deciduous trees that are members of the Salicaceae family, which appear with distinctive leaves and smooth greenish white bark as shown in Fig. 5.1.There are six species of aspen trees found worldwide, excluding hybrid species, Populus grandidentata, Populus tremuloides, Populus tremula, Populus davidiana, Populus sieboldii, and Populus adenopoda (Rogers et al., 2020). It is native to cold regions such as North America, Scotland and Russia (Nesbit et al., 2023). Fig. 5.2 displays the distribution of aspen trees by species. Aspen trees can live for as long as 200 years; according to some studies, they may reach up to 450 years (Latva-Karjanmaa et al., 2007; Vehmas et al., 2009). Due to their crucial role in preserving biodiversity and supporting the ecosystem, aspen trees are particularly vital in colder regions. It provides a range of valuable services to the environment, including carbon storage in the soil, revegetation, serving as forage for livestock, offering shelter to shrubs and herbaceous plants, and even contributing to the production of innovative wood products like paddles, studs, furniture, surgical splints, solid wood, and strand board (Bates & Davies, 2018; Boca & Miegroet, 2017; Gamfeldt et al., 2013; Kivinen et al., 2020; Rogers et al., 2020).